Corrosion-resistant and / or cleanable coated glass substrates

A cerium oxide-coated glass substrate addresses corrosion and cleanability issues by using a cerium oxide layer, enhancing resistance and cleaning efficacy in humid environments.

JP2025502284APending Publication Date: 2025-01-24PILKINGTON GRP LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024542071
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-13
Filing Date
2023-01-12
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing glass substrates suffer from corrosion and reduced cleanability in humid environments, leading to dull appearance and irreparable damage, with existing coatings failing to provide long-term resistance and improved cleaning properties.

Method used

A glass substrate with a cerium oxide layer as the outermost coating, optionally with a silicon oxide underlayer, applied via sputtering or chemical vapor deposition, providing corrosion resistance and enhanced cleanability.

Benefits of technology

The cerium oxide coating significantly reduces corrosion and maintains high cleanability, with minimal haze increase after weathering, ensuring excellent durability and cleaning properties even in harsh conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025502284000001_ABST
    Figure 2025502284000001_ABST
Patent Text Reader

Abstract

The present invention relates to a corrosion-resistant and / or cleanable coated glass substrate comprising an outermost layer comprising 0.5-20 atomic % cerium based on the total composition, and a method for producing a corrosion-resistant and / or cleanable coated glass substrate comprising the step of sputtering a sputtering target comprising cerium to form a layer comprising cerium oxide directly or indirectly on a first surface. The present invention also relates to the use of the layer comprising cerium oxide as a corrosion-resistant and / or cleanable coating on a glass substrate, and to bath, shower and / or splash screens comprising the corrosion-resistant and / or cleanable coated glass substrate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a corrosion-resistant and / or cleanable coated glass substrate, a method for producing the corrosion-resistant and / or cleanable coated glass substrate, the use of a layer comprising cerium oxide as a corrosion-resistant and / or cleanable coating on a glass substrate, and to a bath, shower and / or splash screen comprising the corrosion-resistant and / or cleanable coated glass substrate. [Background technology]

[0002] Coatings on substrates, particularly glass substrates, can be used to modify the properties of the substrate. A variety of methods can be used to deposit coatings on glass substrates, including liquid-based methods including spin coating, dip coating, spray coating, chemical vapor deposition (CVD), and physical vapor deposition (PVD). Physical vapor deposition is also known as sputtering.

[0003] Glass that is in a warm, damp or wet environment becomes more difficult to clean and becomes dull and cloudy in appearance over time. This is due to the relatively harsh conditions that glass is exposed to in a damp or wet environment. Warm, damp environments can cause spots, discoloration, and corrosion on the glass surface. Hard water, soap scum, and cleaning agents can exacerbate the problem. Glass corrosion results in irreparable damage to the glass surface.

[0004] Corrosion of glass occurs in two stages. The first stage is aqueous corrosion, which occurs due to water in contact with the glass surface, leaching alkaline ions from the glass. The second stage involves corrosion occurring even under relatively weakly alkaline conditions, leading to dissolution of the glass surface. Cleaning agents, detergents and soaps used to clean glass surfaces can be weakly or strongly alkaline.

[0005] Attempts have been made to reduce or prevent corrosion of glass by providing surface treatments and / or coatings to the glass.

[0006] Japanese Patent Application Laid-Open No. 8-208275 discloses a weather-resistant and water-resistant glass product in which the glass surface is etched with hydrofluoric acid to a depth of about 4 μm to 6 μm, and then treated with an organic silazane system to make the surface water-repellent.

[0007] EP 2 647 606 A1 relates to glass bath or shower screens intended to mitigate limescale or corrosion by using a silica layer deposited by sputtering. The document discloses that the glass must be doped with at least 8 atomic % silica to prevent corrosion.

[0008] EP 2 559 670 A1 discloses anticorrosive coatings on glass made of alumina, titania, zirconia, or magnesium fluoride with controlled porosity.

[0009] WO 2013 / 003130 describes a method for producing a diamond-like carbon (DLC) and Zn, AlN y , ZnN x or a sacrificial film comprising ZrO2, which is intended to be subjected to a heat treatment prior to use.

[0010] US 2004 / 023080 discloses a protective coating over a functional coating, the protective coating having two layers of sputtered Al2O3 with SiO2 and SiO2 with Al2O3.

[0011] US Patent Publication No. 20200079687 discloses a coated substrate comprising a substrate, a soft coating comprising one or more layers deposited by physical vapor deposition on at least a portion of at least one surface of the substrate, and a sol-gel coating provided on at least a portion of said surface above the soft coating, the sol-gel coating comprising a mixture of titanium oxide, zirconium oxide, silicon oxide, and optionally bismuth oxide and / or cerium oxide in theoretical weight ratios of titanium oxide TiO2 / silicon oxide SiO2 in the range of 0.10-3, zirconium oxide ZrO2 / silicon oxide SiO2 in the range of 0.10-3, bismuth oxide Bi2O3 / silicon oxide SiO2 in the range of 0-0.03, and cerium oxide CeO2 / silicon oxide SiO2 in the range of 0-0.03.

[0012] US Patent Publication No. 2018319701 discloses a method for enhancing the mechanical and chemical resistance of a hydrolyzable network-forming silica gel coating on the surface of a substrate, the method comprising applying to the surface a coating composition comprising a hydrolyzable network-forming silica gel doped with a precursor of bismuth or cerium oxide.

[0013] Additionally, it is also desirable to enhance the cleanability of glass and glazing products. Improved cleanability is associated with a high water contact angle. Products or methods that improve cleanability include surface treatments that render the surface hydrophobic, for example using sol-gel formulations of hybrid organic-inorganic precursors, modified silanes with sol-gel additives, or modified silanes that are chemically crosslinked after surface treatment. Other products include reactive silicone fluids that coat the surface with an easy-to-clean polymer coating, or polymer resins that provide a low-maintenance, non-stick surface. However, many of these treatments do not last the life of the glass sheet.

[0014] Therefore, there remains a need to provide a corrosion resistant glass substrate with long term corrosion and cleaning performance, especially for humid environments. Summary of the Invention

[0015] It is an object of the present invention to overcome the problems associated with known products or methods and to produce glass substrates with no or reduced tendency to corrode and improved cleanability.

[0016] In particular, it would be desirable to provide a glass substrate for moist environments such as bath screens, shower screens, splash screens, car wash view screens, underwater view screens, aquariums, and the like, which provides the above advantages.

[0017] In a first aspect, the present invention provides a corrosion-resistant and / or cleanable coated glass substrate comprising: a glass substrate having a first surface; a layer comprising cerium oxide directly or indirectly on the first surface; the layer comprising cerium oxide is an outermost layer on the first surface; The layer containing cerium oxide contains 0.5 to 20 atomic % of cerium based on the total components. To provide a coated glass substrate that is corrosion resistant and / or cleanable.

[0018] Preferably, the glass substrate is a soda-lime-silica glass substrate, although other glass compositions such as borosilicates, aluminosilicates, boroaluminosilicates, etc. may be used.

[0019] The layer containing cerium oxide is the outermost layer on the first surface. When the layer containing cerium oxide is the outermost layer on the first surface, the layer containing cerium oxide is directly exposed to the environment of the corrosion-resistant glass substrate. When the layer containing cerium oxide is the outermost layer on the first surface, the layer containing cerium oxide has been found to be very effective in improving washability and durability and reducing or preventing corrosion of the glass surface. Therefore, the corrosion-resistant coated glass substrate of the present invention is particularly suitable for use in humid environments such as bath screens, shower screens, splash screens, view screens for car washes, underwater view screens, and aquariums.

[0020] Preferably, the layer comprising cerium oxide is homogeneous in cerium. A layer comprising cerium oxide with homogeneous cerium comprises cerium atoms distributed to a uniform extent throughout the coating layer. Preferably, the cerium atoms are present within an amorphous or semi-amorphous coating layer applied to the first surface, such as one provided by sputtering, constituting the coating layer. Preferably, the cerium atoms are not present within nanoparticles, and preferably the layer comprising cerium oxide does not comprise particles and / or nanoparticles.

[0021] Advantageously, the coated glass is corrosion resistant, as evidenced by a relatively small increase in haze after weathering. Weathering can be accelerated by high humidity, heat, or hot / cold cycles, and for testing purposes, weathering can be simulated by keeping the glass at high temperature with high humidity for a period of time. Typically, the measured haze of the coated glass (e.g., using a haze meter) is 25% or less, preferably 20% or less, more preferably 15% or less, even more preferably 10% or less, and most preferably 5% or less after 50 days at 98% relative humidity and 60°C. Preferably, the corrosion resistant coated glass substrate exhibits a haze increase of 55% or less, more preferably 35% or less, and most preferably 24% or less after 50 days at 98% relative humidity and 60°C. The haze increase can be calculated by comparing the haze measured before and after weathering.

[0022] Typically, the thickness of the layer containing cerium oxide is 1 nm or more, preferably 10 nm or more, more preferably 20 nm or more, and most preferably 30 nm or more. If the coating is too thin, it may not be durable or effective. It is preferred that the thickness of the layer containing cerium oxide is 500 nm or less, preferably 250 nm or less, more preferably 100 nm or less, and most preferably 50 nm or less. If the coating is too thick, cracks may occur during heat treatment or strengthening treatment, which may make production uneconomical.

[0023] Thus, preferably, the layer comprising cerium oxide has a thickness in the range of 1 nm to 500 nm, preferably 5 to 250 nm, more preferably 10 to 100 nm, which is advantageous since it provides a good balance between corrosion protection, durability and economy of production.

[0024] The refractive index of the layer containing cerium oxide is usually in the range of 2.28 to 2.44.

[0025] In some embodiments, it is preferred that the layer comprising cerium oxide is the only layer on the first surface. However, in alternative embodiments, it is preferred to provide an underlayer between the layer comprising cerium oxide and the first surface. Preferably, the underlayer comprises silicon oxide. Such an underlayer may improve the adhesion and durability of the layer comprising cerium oxide. Preferably, the underlayer comprising silicon oxide is disposed directly on the first surface. This further improves the adhesion and durability of the coating on the substrate.

[0026] In a preferred embodiment, the silicon oxide-containing underlayer is disposed directly on the first surface, and the cerium oxide-containing layer is disposed directly on the silicon oxide-containing underlayer, which effectively provides excellent adhesion and durability of the coating layer.

[0027] Preferably, the layer containing cerium oxide contains 1-10 atomic % cerium based on the total composition, and more preferably 2-8 atomic % cerium based on the total composition, such ranges have been shown to provide excellent corrosion resistance and cleanability.

[0028] Preferably, the layer containing cerium oxide has less than a substoichiometric ratio of oxygen.

[0029] Preferably, the layer containing cerium oxide further contains titanium, and preferably, the layer containing cerium oxide contains 50 to 95 atomic % titanium based on titanium and cerium, more preferably, the layer containing cerium oxide contains 70 to 90 atomic % titanium based on titanium and cerium, and even more preferably, the layer containing cerium oxide contains 75 to 85 atomic % titanium based on titanium and cerium.

[0030] Preferably, the layer comprising cerium oxide comprises less than 10 atomic % silicon based on the total composition, preferably, the layer comprising cerium oxide comprises less than 1 atomic % silicon based on the total composition, and more preferably, the layer comprising cerium oxide is essentially free of silicon.

[0031] Preferably, the layer comprising cerium oxide comprises less than 10 atomic % aluminum based on the total composition, preferably, the layer comprising cerium oxide comprises less than 1 atomic % aluminum based on the total composition, and more preferably, the layer comprising cerium oxide is essentially free of aluminum.

[0032] Preferably, the coated glass substrate exhibits a water contact angle of more than 30°, preferably more than 50°, and more preferably more than 60°. Such water contact angles are associated with good cleanability. Thus, according to the present specification, a substrate is cleanable when it exhibits a water contact angle of more than 30°, preferably more than 50°, and more preferably more than 60°.

[0033] The substrate is preferably tempered glass. A tempered glass substrate is particularly advantageous, for example in shower or bath screens and other applications of the present invention, because it enhances user safety. In some cases, the use of tempered glass may be required to comply with legislation. For safety reasons, it is desirable to temper the substrate. If at least one hole is drilled in the substrate, the substrate may be tempered after drilling.

[0034] However, the substrate may be untempered float glass and the coated glass substrate may be supplied to a manufacturer and cut and / or tempered as required. If the substrate is untempered float glass, the coated glass substrate may be referred to as "heat treatable" or "temperable".

[0035] The substrate may be adapted to hold a fixture for securing the substrate in place during use The substrate may be adapted to hold the fixture by drilling at least one hole (e.g., one hole, two holes, three holes, four holes, or more than three holes) in the substrate.

[0036] The substrate is preferably edged.

[0037] According to a second aspect of the present invention, there is provided a method for producing a corrosion-resistant and / or cleanable coated glass substrate, preferably a corrosion-resistant coated glass substrate according to the first aspect of the present invention, comprising the steps of: Providing a glass substrate having a first surface; providing a sputtering target comprising cerium; sputtering a sputtering target comprising cerium to provide a layer comprising cerium oxide directly or indirectly on the first surface; The present invention provides a method comprising:

[0038] Such a process provides a coated glass substrate that is corrosion resistant.

[0039] Preferably, the glass substrate is a soda-lime-silica glass substrate, although other glass compositions such as borosilicates, aluminosilicates, boroaluminosilicates, etc. may be used.

[0040] Preferably, the sputtering target comprises titanium, preferably 50-95 atomic % titanium based on titanium and cerium, more preferably the sputtering target comprises 70-90 atomic % titanium based on titanium and cerium, and even more preferably the sputtering target comprises 75-85 atomic % titanium based on titanium and cerium. The inclusion of titanium in the sputtering target increases the electrical conductivity of the sputtering target and increases the rate of the sputtering process.

[0041] Preferably, the step of sputtering the sputtering target is carried out in an atmosphere containing less than 10% by volume of oxygen, preferably less than 5% by volume of oxygen, more preferably less than 1% by volume of oxygen. Those skilled in the art can evaluate the sputtering atmosphere based on the flow rate of the sputtering atmosphere gas. Preferably, the step of sputtering the sputtering target is carried out in an atmosphere containing a noble gas, preferably the noble gas is argon or krypton. Preferably, the sputtering atmosphere is more than 50% by volume of a noble gas, preferably argon, more preferably more than 90% by volume of a noble gas, preferably argon.

[0042] If the sputtering step is carried out in an oxygen-poor atmosphere, the oxygen atoms provided to the coating may be provided by the target. A sputtering target that contains a significant proportion of oxygen may be considered "ceramic". Thus, the sputtering target is preferably a ceramic sputtering target.

[0043] Preferably, the sputtering step is a plasma sputtering step. By using the plasma sputtering method, a film of uniform quality can be obtained, and the adhesion of the film is also high. In some cases, a large-scale target can be used, so that a film can be produced on a large glass size. The plasma sputtering method includes DC sputtering, RF sputtering, magnetron sputtering, and reactive sputtering. Preferably, the layer containing cerium oxide is produced by magnetron sputtering. First, an appropriate amount of argon gas and, if necessary, oxygen gas that can apply a voltage to the cathode on which the target material is placed are introduced into the vacuum chamber. At this time, electrons emitted from the cathode collide with gas atoms of the Ar gas, thereby causing the Ar gas atoms to be converted into Ar. + The argon is ionized into ions. At this time, the argon is excited and releases electrons, releasing energy. This causes a glow discharge. The glow discharge creates a plasma in which ions and electrons coexist. Ar in the plasma + The ions are accelerated by a large potential difference towards a cathode target and collide with the target's surface, displacing target atoms and propelling them towards the substrate, forming a coating layer.

[0044] Preferably, the method further comprises cleaning the surface before sputtering the sputtering target. Such a step may improve the durability and / or appearance of the coating layer. Preferably, the cleaning of the surface comprises one or more of polishing with ceria, cleaning with an aqueous alkaline solution, rinsing with deionized water, and plasma treatment. Additionally or alternatively, other cleaning methods may be used as known to those skilled in the art.

[0045] Preferably, the sputtering target is a cylindrical sputtering target, which may be used to improve the uniformity of the coating layer produced and / or provide high quality coatings in a repeatable manner.

[0046] The substrate may be strengthened prior to applying the layer comprising cerium oxide. However, it is most preferred that it is strengthened by a heat treatment step after applying the layer comprising cerium oxide. Therefore, preferably, the process further comprises a step of heat treating the soda-lime-silica glass substrate after the step of sputtering the sputtering target, and preferably, the step of heat treating the soda-lime-silica glass substrate comprises heating the soda-lime-silica glass substrate at at least 600° C. for at least 5 minutes.

[0047] The inventors have discovered that the cerium oxide-containing layer produced by the present method is suitable for such heat treatment because it is not significantly damaged as evidenced by minimal changes in transparency, haze, and durability after heat treatment. The cerium oxide-containing layer is therefore considered to be "heat treatable". This is highly beneficial as it allows glass manufacturers to apply the coating on a large scale and then cut and strengthen it as required by the manufacturer of bath screens, shower screens, etc. Thus, it may provide manufacturers with a high quality corrosion resistant coating without requiring changes to their processing procedures.

[0048] As mentioned above, in some embodiments, the corrosion-resistant coated glass substrate may include an underlayer between the layer containing cerium oxide and the first surface, preferably the underlayer includes silicon oxide. If the coated glass substrate includes an underlayer, it may be formed by the same or different coating method as the coating method of the layer containing cerium oxide.

[0049] In one embodiment, the underlayer, preferably a silicon oxide underlayer, is produced by a sputtering method and the layer containing cerium oxide is produced by a sputtering method, which makes it possible to obtain a high quality product. A person skilled in the art knows how to provide a layer such as the underlayer by sputtering.

[0050] In another embodiment, the underlayer, preferably a silicon oxide underlayer, is produced by chemical vapor deposition during the float process, preferably by "on-line" chemical vapor deposition, and the layer containing cerium oxide is produced by sputtering. This may increase the production speed of the product. The deposition of the silicon oxide layer using chemical vapor deposition, also known as pyrolytic deposition, may be carried out as disclosed in US Patent Application Publication No. 2018118613, which is incorporated herein by reference. Typically, pyrolytic deposition of the underlayer involves contacting the surface of the substrate with a precursor mixture comprising a silicon source, an oxygen source, and optionally a radical scavenger. The silicon source may comprise an oxygenated silicon compound, such as, for example, a silicon alkoxide (e.g., tetraethyl orthosilicate, TEOS) and / or a silicon halide (e.g., silicon chloride). However, preferably, the silicon source comprises a silane, more preferably a monosilane, SiH4. The pyrolytic deposition of silicon oxide may be advantageously carried out in combination with the production of glass substrates in the well-known float glass manufacturing process. It was found that the chemical vapor deposition produced silicon oxide underlayer improved the durability of the coating compared to the sputtered silicon oxide underlayer, and furthermore, the measured water contact angle of the cerium oxide-containing coating was improved with the chemical vapor deposition produced silicon oxide underlayer compared to the cerium oxide-containing coating with the sputtered silicon oxide underlayer.

[0051] In some embodiments, the underlayer may be applied to the first surface by applying a liquid coating precursor, preferably a liquid coating precursor comprising a silazane, preferably a polysilazane, or an orthosilicate, preferably tetraethyl orthosilicate (TEOS). Methods of producing an underlayer from a liquid coating precursor comprising a polysilazane are disclosed, for example, in WO2017187173, which is incorporated herein by reference. The method of applying the liquid coating precursor to the surface is generally not critical and may use a variety of techniques. The method of contacting the surface with the coating composition may include, for example, a method selected from dip coating, spin coating, roller coating, spray coating, air atomized spray, ultrasonic spray, and / or slot die coating. Preferably, the liquid coating precursor is cured after application to form the coating.

[0052] According to a third aspect of the invention there is provided the use of a layer comprising cerium oxide as a corrosion resistant and / or cleanable coating on a glass substrate, comprising: the glass substrate having a first surface; the layer comprising cerium oxide is directly or indirectly present on the first surface; the layer comprising cerium oxide is an outermost layer on the first surface; The layer containing cerium oxide is provided with a use containing 0.5 to 20 atomic % of cerium based on the total components.

[0053] Preferably, the glass substrate is a soda-lime-silica glass substrate, although other glass compositions such as borosilicates, aluminosilicates, boroaluminosilicates, etc. may be used.

[0054] According to a fourth aspect of the present invention there is provided a bath, shower and / or splash screen comprising a corrosion resistant and / or cleanable coated glass substrate according to the first aspect or manufactured according to the second aspect.

[0055] Preferably, the bath screen and / or shower screen further comprises a fastener for fixing the bath screen and / or shower screen in a position of use. Typically, the fastener comprises an adhesive or mechanical attachment for attaching the fastener to the splash screen. Such fasteners may include hinge fasteners. The fastener may be attached to the splash screen by adhesive (e.g., attaching an adhesive pad to at least one surface of the splash screen and to the fastener) and / or mechanical attachment (e.g., bolts), passing through or attached to holes in the splash screen. Such holes may be drilled holes.

[0056] Those skilled in the art will appreciate that any optional or preferred features of an embodiment of the present invention may also be applied to other embodiments depending on their needs and requirements.

[0057] The invention will now be described, by way of example only, with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0058] [Figure 1] FIG. 1 shows a schematic diagram of a coated substrate according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic diagram of a coated substrate with an underlayer according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0059] FIG. 1 illustrates diagrammatically a coated glass substrate 1 comprising a substrate of soda-lime-silica glass 2 having a first surface 21 and a layer 3 comprising cerium oxide formed directly on the first surface 21, the layer 3 comprising cerium oxide being the outermost layer on the first surface 21.

[0060] 2 illustrates diagrammatically a coated glass substrate 1 comprising a substrate of soda-lime-silica glass 2 having a first surface 21 and a layer 3 comprising cerium oxide disposed indirectly on the first surface 21, the layer 3 comprising cerium oxide being the outermost layer on the first surface 21, and further comprising an underlayer 4 between the layer 3 comprising cerium oxide and the first surface 21, the underlayer 4 being disposed directly on the first surface 21. Preferably, the underlayer 4 comprises silicon oxide. EXAMPLES

[0061] The present invention is further illustrated by, but not limited to, the following examples.

[0062] An example according to the invention was prepared by sputtering a rotatable ceramic target 23 inches long and 5.914 inches in diameter containing 65% by weight TiO2 and 35% by weight CeO2 (equivalent to 80.0 atomic % titanium and 20.0 atomic % cerium on a cerium and titanium basis, and 26.7 atomic % titanium, 6.7 atomic % cerium, and 66.7 atomic % oxygen on a total component basis). Cerium, Titanium, and Oxygen CeTiO x A layer containing

[0063] Examples 1 to 3 are CeTiO x The layers containing CeTiO were prepared by sputtering them directly onto a soda-lime-silica glass substrate, and Examples 4 to 6 were prepared by sputtering a layer containing CeTiO x The layer comprising was fabricated by sputtering onto an underlayer comprising silicon oxide. In these examples, the underlayer comprising silicon oxide was prepared using chemical vapor deposition to a thickness of 20-30 nm.

[0064] When the examples and comparative examples were subjected to heat treatment, this was at a temperature of 650° C. for 5 minutes.

[0065] (Description of the embodiment) The coated substrates were tested for optical properties (according to ISO 9050), water contact angle (50 μl deionized water drop) and resistance to corrosion due to humidity.

[0066] Table 1 shows the average water contact angles (n=5) for 10x10 cm samples measured as-deposited (AD), after heat treatment and aging in air for 2 weeks (HT 2 weeks), and after heat treatment and aging in air for 3 weeks (HT 3 weeks). Water contact angles were measured with deionized water using an FTA200 equipped with FTA32 software, both available from First Ten Angstroms, Newark, CA, USA.

[0067] [Table 1]

[0068] From Table 1, untreated glass has a water contact angle of 25°, compared to 1.0° for CeTiO x It can be seen that the use of the coating of the present invention results in substrates with surprisingly high water contact angles of over 60°. High water contact angles translate into improved cleanability. Thus, by applying the coating of the present invention, a cleanable substrate is produced.

[0069] In fact, high water contact angles can be obtained with coatings as thin as 10 nm, which are surprisingly long-lasting. x The coatings yield surprisingly high water contact angles, and the aging performance of such coatings is significantly improved by the presence of a silicon oxide underlayer. Similarly, a 25 nm CeTiO x The aging performance of the coating is improved by the presence of a silicon oxide underlayer.

[0070] Thus, in embodiments where a silicon oxide underlayer is desired, CeTiO xThe layer thickness is preferably greater than 10 nm, more preferably 25 nm or more, more preferably 50 nm or more, for example, 10 nm to 500 nm, preferably 25 nm to 250 nm, more preferably 50 nm to 100 nm. It was confirmed that the water contact angle increases with aging to a stable value.

[0071] The examples and comparative examples were subjected to an alkaline corrosion test, where the heat treated samples were immersed in 1 M NaOH for 2 hours at 23° C. The change in haze was evaluated according to ASTM D1003 (BYK Gardner Haze-gard plus) as shown in Table 2, and the change in transmittance was evaluated as shown in Table 3.

[0072] [Table 2]

[0073] [Table 3]

[0074] Table 2 shows that all the measured samples showed very low haze both at the start of the test and after the alkaline corrosion test, and the CeTiO x Similarly, Table 3 shows that the CeTiO coating exhibits excellent corrosion resistance. x It is shown that the transmittance decreases with increasing coating thickness, but the presence of a silicon oxide underlayer increases or only slightly decreases the transmittance. The change in transmittance due to alkaline corrosion testing is negligible.

[0075] The examples and comparative examples were subjected to an acid etching test, where the heat treated samples were immersed in 1 M HCl for 2 hours at 23° C. The change in haze was evaluated according to ASTM D1003 (BYK Gardner Haze-gard plus) as shown in Table 2, and the change in transmittance was evaluated as shown in Table 3.

[0076] [Table 4]

[0077] Table 4 shows that all the samples measured showed extremely low haze both at the start of the test and after the acid corrosion test, and the CeTiO x This indicates that the coating provides excellent corrosion resistance.

[0078] [Table 5]

[0079] Table 5 shows that the change in transmittance due to the acid etching test is negligible.

[0080] Therefore, CeTiO x The coatings can be used to produce heat-treated coated glass substrates with excellent cleanability and excellent corrosion resistance. Furthermore, because the coated glass substrates are highly responsive to heat treatment, heat-treatable coated glass substrates are provided which can be heat-treated to produce heat-treated coated glass substrates with excellent cleanability and excellent corrosion resistance.

Claims

1. A corrosion-resistant and / or cleanable coated glass substrate, comprising: a glass substrate having a first surface; a layer comprising cerium oxide directly or indirectly on the first surface; the layer comprising cerium oxide is an outermost layer on the first surface; The layer containing cerium oxide contains 0.5 to 20 atomic % of cerium based on the total composition. A corrosion resistant and / or cleanable coated glass substrate.

2. 10. The coated glass substrate of claim 1, wherein the coated glass substrate exhibits an increase in haze of 1% or less after immersion in 1 M NaOH or 1 M HCl at 23°C for 2 hours.

3. 3. The coated glass substrate according to claim 1 or 2, wherein the layer comprising cerium oxide has a thickness of 1 nm to 500 nm, preferably 5 nm to 250 nm, more preferably 10 nm to 100 nm.

4. 4. The coated glass substrate of claim 1, wherein the layer comprising cerium oxide has a refractive index in the range of 2.28 to 2.

44.

5. 5. The coated glass substrate of claim 1, wherein the layer comprising cerium oxide is the only layer on the first surface.

6. 5. The coated glass substrate of claim 1, further comprising an underlayer between the layer comprising cerium oxide and the first surface.

7. 7. The coated glass substrate of claim 6, wherein the underlayer comprises silicon oxide, preferably the underlayer comprising silicon oxide is directly on the first surface, more preferably the underlayer comprising silicon oxide is directly on the first surface and the layer comprising cerium oxide is directly on the underlayer.

8. 8. The coated glass substrate according to claim 1 , wherein the layer comprising cerium oxide comprises 1 to 10 atomic % cerium based on the total composition, preferably 2 to 8 atomic % cerium based on the total composition.

9. 9. The coated glass substrate of claim 1, wherein the layer comprising cerium oxide is less than substoichiometric in oxygen.

10. 10. The coated glass substrate of any one of claims 1 to 9, wherein the layer comprising cerium oxide further comprises titanium, preferably the layer comprising cerium oxide comprises 50 to 95 atomic % titanium based on titanium and cerium, more preferably the layer comprising cerium oxide comprises 70 to 90 atomic % titanium based on titanium and cerium, even more preferably the layer comprising cerium oxide comprises 75 to 85 atomic % titanium based on titanium and cerium.

11. 11. The coated glass substrate of claim 1, wherein the layer comprising cerium oxide comprises less than 10 atomic % silicon based on the total composition, preferably the layer comprising cerium comprises less than 1 atomic % silicon based on the total composition, more preferably the layer comprising cerium is essentially free of silicon.

12. 12. The coated glass substrate of claim 1, wherein the layer comprising cerium oxide comprises less than 10 atomic % aluminum based on the total composition, preferably the layer comprising cerium comprises less than 1 atomic % aluminum based on the total composition, more preferably the layer comprising cerium is essentially free of aluminum.

13. 13. The coated glass substrate according to any one of claims 1 to 12, wherein the coated glass substrate exhibits a water contact angle of greater than 30°, preferably greater than 50°, more preferably greater than 60°.

14. 14. The coated glass substrate of claim 1, wherein the substrate is tempered glass.

15. 15. A method for producing a corrosion-resistant and / or cleanable coated glass substrate, preferably a corrosion-resistant coated glass substrate according to any one of claims 1 to 14, comprising the steps of: Providing a glass substrate having a first surface; providing a sputtering target comprising cerium; sputtering a sputtering target comprising cerium to provide a layer comprising cerium oxide directly or indirectly on the first surface; A method comprising:

16. 16. The method of claim 15, wherein the sputtering target comprises titanium, preferably 50-95 atomic % titanium based on titanium and cerium, more preferably the sputtering target comprises 70-90 atomic % titanium based on titanium and cerium, and even more preferably the sputtering target comprises 75-85 atomic % titanium based on titanium and cerium.

17. 17. The method according to claim 15 or 16, wherein the step of sputtering the sputtering target is carried out in an atmosphere comprising a noble gas, preferably the noble gas being argon or krypton.

18. 18. The method of any one of claims 15 to 17, further comprising a step of cleaning the surface prior to sputtering the sputtering target, preferably the step of cleaning the surface comprises one or more of polishing with ceria, cleaning with an aqueous alkaline solution, rinsing with deionized water, and plasma treatment.

19. 19. The method of any one of claims 15 to 18, wherein the sputtering target is a cylindrical sputtering target.

20. 20. The method of any one of claims 15 to 19, further comprising a step of heat treating the soda-lime-silica glass substrate after the step of sputtering the sputtering target, preferably wherein the step of heat treating the soda-lime-silica glass substrate comprises heating the soda-lime-silica glass substrate at at least 600°C for at least 5 minutes.

21. 21. The method of any one of claims 15 to 20, further comprising the step of applying an underlayer to the first surface prior to the step of sputtering the sputtering target, preferably wherein the step of applying an underlayer comprises depositing a layer comprising silica by chemical vapor deposition, physical vapor deposition, or liquid deposition, preferably by chemical vapor deposition.

22. 1. Use of a layer comprising cerium oxide as a corrosion-resistant and / or cleanable coating on a glass substrate, comprising the glass substrate having a first surface; the layer comprising cerium oxide is directly or indirectly on the first surface; the layer comprising cerium oxide is an outermost layer on the first surface; The layer containing cerium oxide contains 0.5 to 20 atomic % of cerium based on the total composition. Use of a layer comprising cerium oxide as a corrosion-resistant and / or cleanable coating on a glass substrate.

23. 22. A bath, shower and / or splash screen comprising a corrosion resistant and / or cleanable coated glass substrate according to any one of claims 1 to 14 or manufactured according to the method according to any one of claims 15 to 21.

24. 24. A bath, shower and / or splash screen as claimed in claim 23, further comprising a fixing for fixing the bath and / or shower screen in a position of use, preferably the fixing comprising an adhesive or mechanical attachment part for attaching the fixing to the splash screen.

Citation Information

Patent Citations

  • Ultraviolet / Heat ray-shielding film and glass provided therewith and method therefor

    JP1994144870A

  • Ultraviolet-ray cut film, film forming target and production thereof

    JP1995070743A

  • Optical thin film, composition for forming the same and heat ray reflecting glass using the same

    JP1998120441A

  • Coated Substrate

    JP2020519553A